Design and Optimization of a Reconfigurable Photovoltaic Generator - GHEZAL, Amir; RIGUET, Manal Oumaima; Enca/ Benhamadouche (university of M'sila, 2021)
In this thesis, we presented our work which is interested in the design of reconfigurable photovoltaic systems. This work allowed us to understand and overcome the different topologies that a PV generator can have. These topologies improve the behavior of a PV system in the face of the risk of malfunctions such as partial shading. The work presented is based on the dynamic optimization of the topology when the photovoltaic field is subjected to partial shading. For this, several shading scenarios are discussed and all possible reconfigurations of the photovoltaic generator are studied. An algorithm is then performed to track down and put the PV array into a configuration that reduces power loss in partially shaded conditions.